Sebuah Kasus : Laki-Laki 17 Tahun dengan Tuberkulosis Intestinal - Nursadilah Nursadilah; Marliza Marliza (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Extrapulmonary tuberculosis (TB) is a TB infection that attacks organs other than the lungs such as the pleura, lymph nodes, gastrointestinal tract, genitourinary tract, skin, bones, joints and lining of the brain. Patients with extrapulmonary TB often present with symptoms and signs related to the site of involvement. Systemic symptoms (such as weight loss, fever, hyperhidrosis, dyspnea, malaise) are usually present, although not always present. In clinical practice, it is not uncommon for extra pulmonary TB in an unclear location to be detected incidentally. The diagnosis of Intestinal TB is sometimes difficult to make and is only known after the disease. Therefore, some experts recommend empiric OAT therapy even though a definite diagnosis has not yet been established. This is done mainly in patients from endemic areas. This case report presents a 17 year old male with complaints of abdominal pain. Complaints accompanied by decreased appetite and drastic weight loss. The patient underwent a number of therapies in the form of drugs and surgery. The patient's condition improved after treatment and he was able to go home provided he had to be checked again periodically.